2022
DOI: 10.1111/ijet.12344
|View full text |Cite
|
Sign up to set email alerts
|

Vertical cross‐ownership, input price discrimination, and social welfare

Abstract: In this paper, we analyze the impact of vertical cross‐ownership with input price discrimination on social welfare. A higher degree of product differentiation will raise industry profit, consumer surplus, and social welfare; under forward cross‐ownership, a higher degree of cross‐ownership has the same effect, in addition, it will reduce rival firm's profit and increase upstream firm's profit; however, under backward cross‐ownership, a higher degree of cross‐ownership has an opposite effect. Furthermore, under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 22 publications
(26 reference statements)
1
5
0
Order By: Relevance
“…Forward cross‐ownership is beneficial for consumers and the society. This result is also obtained in Sun and Wang (2023) who stated that forward cross‐ownership will improve consumer and social welfare under input price discrimination.…”
Section: Vertical Cross‐ownership and Social Welfaresupporting
confidence: 77%
See 1 more Smart Citation
“…Forward cross‐ownership is beneficial for consumers and the society. This result is also obtained in Sun and Wang (2023) who stated that forward cross‐ownership will improve consumer and social welfare under input price discrimination.…”
Section: Vertical Cross‐ownership and Social Welfaresupporting
confidence: 77%
“…In particular, when the ownership structure is given, input price discrimination will improve welfare in the short run; however, the effect of input price discrimination on shareholding will achieve the same result in the long run. Sun and Wang (2023) further demonstrated that under forward cross‐ownership, a higher degree of cross‐ownership will reduce rival firm's profit and increase upstream firm's profit; however, under backward cross‐ownership, a higher degree of cross‐ownership has an opposite effect. Furthermore, under the Cournot and Bertrand competition, forward cross‐ownership will incentivize downstream firms to produce more via a lower input price, achieving the above effect.…”
Section: Introductionmentioning
confidence: 99%
“…The primary conclusion is that the existence of cross‐ownership increases social welfare, provided that product differentiation is not significant. Sun and Wang (2022) investigated the effect of cross‐ownership on social welfare in a vertically related market with input discrimination. They found that under forward cross‐ownership, a higher degree of cross‐ownership raises producer surplus, consumer surplus, and social welfare.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In this paper, a vertically related market with vertical product differentiation is used to analyze the impact of vertical cross-ownership on industry profit, consumer surplus and social welfare. It is highly related with Sun and Wang (2022) who analyze the impact of vertical cross ownership with input price discrimination on social welfare under both forward and backward cross ownership with horizontal product differentiation. In our model setting, we find that when the upstream firm holds the share of the low-quality downstream firm, the industry profit is increasing (decreasing) in the cross-ownership if the product quality difference is large (small); however, when the upstream firm holds the share of the high-quality downstream firm, the industry profit is increasing in the cross-ownership.…”
Section: Introductionmentioning
confidence: 99%